2022
DOI: 10.2486/indhealth.2020-0259
|View full text |Cite
|
Sign up to set email alerts
|

Work strain and thermophysiological responses in Norwegian fish farming — a field study

Abstract: Fish farming is considered as a physical demanding occupation, including work operations with high workloads and awkward work positions for prolonged periods of time.Combined with potential challenging environmental conditions, these factors may negatively affect work performance, comfort and health. This study aimed to explore work strain and thermophysiological responses in Norwegian fish farming. Fourteen workers (age 35 ± 15 yrs) from four fish farms participated in the field studies, and measurements of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The most common heat-related health outcome assessed was HRI (n = 57; 62%). Twenty-seven out of 57 of these studies relied on selfreported HRI symptoms (25,27,30,(40)(41)(42), while 21 measured various physiological parameters such as core body temperature, skin temperature, heart rate, blood pressure, changes in body weight, or urine specific gravity (61,68,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88). Another commonly assessed heat-related health outcome was kidney disease (n = 28; 30%).…”
Section: Descriptive Characteristics Of Included Studiesmentioning
confidence: 99%
“…The most common heat-related health outcome assessed was HRI (n = 57; 62%). Twenty-seven out of 57 of these studies relied on selfreported HRI symptoms (25,27,30,(40)(41)(42), while 21 measured various physiological parameters such as core body temperature, skin temperature, heart rate, blood pressure, changes in body weight, or urine specific gravity (61,68,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88). Another commonly assessed heat-related health outcome was kidney disease (n = 28; 30%).…”
Section: Descriptive Characteristics Of Included Studiesmentioning
confidence: 99%
“…High levels of occupational physical activity (OPA) increase the likelihood of cardiovascular problems and musculoskeletal disorders. These factors affect the work performance, comfort, and health of the workers negatively (Sandsund et al 2022). Ngaruiya et al (2019) found 2.78 million worker medical deaths annually.…”
Section: Literature Reviewmentioning
confidence: 99%